The epistemological foundation of the erga omnes obligations in public international law - Piemonte Ditão, Ygor Pierry (Revista de Direito Internacional e Globalização Econômica, 2023)
The present work presents the epistemological foundation for the existence of erga omnes obligations in International Law, making use, for that purpose, of the foundationalist theory of epistemology through reductionism to methodological individualism, verifying, first, human nature, then, the nature of Law passing to Domestic Law to, finally, demonstrate that erga omnes obligations are sine qua non for the existence of International Law, without which it will become a simple political science (international relations), through the bibliographic review and the method inductive.